Expression of Sphingosine-1-phosphate (S1P) on the cerebral vasospasm after subarachnoid hemorrhage in rabbits - Tang,Hua (2015)
PURPOSE: To demonstrate the relationship between of sphingosine-1-phosphate (S1P) expression and subarachnoid hemorrhage (SAH). METHODS: The basilar arteries from a "double-hemorrhage" rabbit model of SAH were used to investigate the relation between S1P expression and SAH. Various symptoms, including blood clots, basilar artery cross-sectional area, and S1P phosphatase expression were measured at day 3, 5, 7, 9. RESULTS: The expression of S1P was enhanced in the cerebral vasospasm after subarachnoid hemorrhage in the rabbits. And S1P expression was consistent with the basilar artery cross-sectional area changes at day 3, 5, 7, 9. CONCLUSION: Sphingosine-1-phosphate expression in the cerebral arterial may be a new indicator in the development of cerebral vasospasm after subarachnoid hemorrhage and provide a new therapeutic method for SAH.